Knowledge–practice concordance and discrepancies in very old adults - Aline Schönenberg; Jenny M. Ruttloff; Konstantin G. Heimrich; Tino Prell (Frontiers in Medicine, 2026)
Background Health-related knowledge is often considered a prerequisite for health behavior, but knowledge may not always translate into everyday practice. This study examined concordance and directional discrepancies between self-reported health-related knowledge and practice among very old adults. Methods We analyzed data from 2,919 participants aged 80 years and older from the nationally representative Old Age in Germany (D80+) study (CATI Module 2). Health-related knowledge and self-reported health-related practice were assessed using ordinal self-report items. A positive knowledge–practice discrepancy was defined as reported knowledge exceeding reported practice. CATI2-calibrated complex-survey descriptive analyses were used to examine knowledge–practice patterns. Complex-survey logistic regression models examined factors associated with the presence of a positive discrepancy, while linear models examined its magnitude as a secondary outcome. Exploratory age-, sex-, and education-adjusted models compared the health, functional, and psychosocial profiles of participants with and without a positive discrepancy. Results Most participants reported the highest category of health-related knowledge (74.2, 95% CI 71.8 to 76.5%) and self-reported practice (73.7, 95% CI 71.3 to 76.0%). Knowledge and practice were concordant in 76.5% of participants (95% CI 74.4 to 78.6%), whereas 12.2% showed a positive knowledge–practice discrepancy (95% CI 10.5 to 13.9%). In fully adjusted complex-survey models, higher internal control experience was associated with lower odds of a positive knowledge–practice discrepancy and with a smaller discrepancy magnitude. In exploratory health-profile analyses, positive discrepancy status was associated with lower ADL and IADL scores, more depressive symptoms, lower life satisfaction, more negative aging experiences, and lower internal control experience; these associations remained significant after false-discovery-rate correction. Conclusion In very old adults, knowledge and practice were generally concordant, while a minority reported more knowledge than practice. Positive discrepancy status co-occurred with a less favorable functional and psychosocial profile, and internal control experience was the most consistent cross-sectional correlate. Longitudinal and behavior-specific studies are needed to clarify the direction and practical relevance of these associations.